The sun and the star : a Nico di Angelo adventure - Riordan, Rick; Oshiro, Mark (Disney/Hyperion, 2023)
In this spin-off story from the Percy Jackson series, demigod Nico di Angelo, the son of Hades begins dreaming that a voice is calling to him from Tartarus, the deepest part of the Underworld. Nico thinks it's Bob, a Titan who saved his friends and is now trapped there. With help from his boyfriend, Will Solace, the son of Apollo, Nico finds a prophecy that can help him find a way there, but the prophecy has a foreboding warning that may prevent Nico and Will from returning.